EVALUATION OF QUALITY OF EDUCATION AS A TOOL FOR EVALUATING THE ACTIVITY OF KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN: EVALUATION OF QUALITY OF EDUCATION AS A TOOL FOR EVALUATING THE ACTIVITY OF KONSTANTIN PRESLAVSKY UNIVERSITY OF SHUMEN - Todorova , Korneliya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article presents an empirical study of the quality evaluation of education at Konstantin Preslavsky University of Shumen from two perspectives – the faculty staff and students. Special attention is given to certain features of the learning process, which should be regarded as indicators of quality.